Optimalisasi Peran Mahasiswa Dalam Penguatan 4 Keterampilan Bahasa Melalui Materi Adverb Of Frequency Bagi Siswa MTS Hidayatul Insan Palangka Raya - Syarif Hidayat; Zaitun Qamariah; Hesty Widiastuty (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
The collaborative community service activity between the lecturers and students at MTs Hidayatul Insan aims to enhance the learning experience and academic support for students under the title "Optimizing Student Role in Strengthening 4 Language Skills Through Adverb of Frequency Material for Students of Mts Hidayatul Insan Palangka Raya." This initiative focuses on improving language skills, particularly in the use of adverbs of frequency for the students. Through interactive workshops, classroom sessions, and practical exercises, the lecturers and students work together to develop engaging and effective teaching materials tailored to the needs of the students. The collaborative effort fosters a conducive learning environment and promotes active engagement